Effects of customized foot orthoses on manufacturing workers in the metal industry. Issue 1 (2nd January 2016) - García-Hernández, César; Huertas-Talón, José-Luis; Sánchez-Álvarez, Eduardo J.; Marín-Zurdo, Javier
Abstract : This 8-week study evaluates the effects of customized foot orthoses on work-related musculoskeletal disorders (WMSDs) of metal industry workers. These WMSDs were evaluated applying the Nordic musculoskeletal questionnaire (NMQ) at three different times (start, 4th week and 8th week) and additional questions were also formulated to obtain information about adaptation, fatigue, comfort and possible improvements. According to the NMQ results, statistical significance was found in the improvements after 4 weeks ( p  < 0.05 in two areas, p  < 0.01 in three areas, p  < 0.001 in two areas and no significance in the other two) and after 8 weeks ( p  < 0.01 in three areas, p  < 0.001 in four areas and no significance in the other two). The additional questions indicated fatigue reduction (both in general and in lower extremity), comfort level increase (after the adaptation period) and good acceptance, according to workers' answers, suggesting customized orthoses can be effective in reducing and preventing WMSDs in several body regions.